Sekularisasi Sinyal Keagamaan Pada Pasar Multikultural: Model Jalur Ganda Konsumsi Halal Di Indonesia - M. Afif Shahputra Zen; Saparuddin Siregar; Sugianto Sugianto; Muhammad Habibi Siregar (Inovasi, 2026)
This study aims to deconstruct the psychological architecture of consumer preferences for halal products within a multicultural market transitioning toward a mandatory certification regime. Amidst the theoretical schism between religious approaches (Theory of Planned Behavior) and utilitarian perspectives (Lancaster’s Theory), this research proposes an integrative model to explain how a single religious symbol acts as a driver for consumption across diverse faith groups simultaneously. Employing a Mixed-Methods Sequential Explanatory design, this study analyzed data from 182 respondents in Medan City using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Multi-Group Analysis (MGA), followed by a qualitative deepening through Reflexive Thematic Analysis of 25 informants. The MGA results reveal a sharp and statistically significant behavioral divergence. In the Muslim group, the direct pathway from religion to preference is substantial (β = 0.293), driven by a mechanism of "Transcendental Compliance" which is largely inelastic. Conversely, in the Non-Muslim group, the influence of religion is negligible (β = 0.002). Qualitative findings illuminate this statistical anomaly through the phenomenon of "Symbol Secularization," where Non-Muslim consumers deconstruct the halal label from its theological attributes and reconstruct it as a functional indicator of quality assurance and hygiene (Hifz al-Nafs). The primary conclusion of this study is that market equilibrium is achieved because the halal label operates as a Polysemic Signal; a single visual signifier that transmits meanings of "sanctity" for the in-group (Muslim) and "quality assurance" for the out-group (Non-Muslim) concurrently. This research recommends that industry players adopt ambidextrous marketing strategies, emphasizing universal quality standards without compromising the authenticity of Sharia values. Keywords: Halal Certification, Multicultural Market, Polysemic Signal, Symbol Secularization, Multi-Group Analysis, Mixed-Methods.